Auditoría tributaria en la ferretería Pujilí, ubicada en la parroquia Pujilí del cantón Pujilí provincia de Cotopaxi, al periodo del 01 de enero al 31 de diciembre del 2013 - Tacuri Jácome, Aída del Pilar (2015)
This research work is part of a tax audit that was performed at the Hardware Pujilí, in order to carry out a study for the implementation and verification of payment of tax obligations affecting the economy in order to identify shortcomings that prevent compliance efficient when the SRI report taxes. To establish excellent results in the application and tax compliance is essential to collect real and correct information, the same which is provided solely by the accountant of the hardware, using techniques such as observation, interview and survey, in which we found the following shortcomings: the hardware does not have a counter plan, submitting tax obligations takes place in late, there is ignorance on the part of the staff responsible for billing….